Idiopathic subglottic stenosis is associated with activation of the inflammatory IL‐17A/IL‐23 axis. (14th June 2016) - Gelbard, Alexander; Katsantonis, Nicolas‐George; Mizuta, Masanobu; Newcomb, Dawn; Rotsinger, Joseph; Rousseau, Bernard; Daniero, James J.; Edell, Eric S.; Ekbom, Dale C.; Kasperbauer, Jan L.; Hillel, Alexander T.; Yang, Liying; et al.
Abstract : Objectives/Hypothesis: Idiopathic subglottic stenosis (iSGS) is a rare and devastating extrathoracic obstruction involving the lower laryngeal and upper tracheal airway. It arises without known antecedent injury or associated disease process. Persistent mucosal inflammation and a localized fibrotic response are hallmarks of the disease. Despite the initial clinical description of iSGS more than 40 year ago, there have been no substantive investigations into the pathogenesis of this enigmatic and progressive airway obstruction. In these studies, we present the initial characterization of the molecular pathogenesis underlying the fibrosing phenotype of iSGS. Methods: Utilizing 20 human iSGS and healthy control specimens, we applied histologic, immunohistochemical, molecular, and immunologic techniques. Results: We demonstrate significant activation of the canonical IL‐23/IL‐17A pathway in the tracheal mucosa of iSGS patients, as well as identify γδ T cells as the primary cellular source of IL‐17A. Conclusion: Our results suggest that aberrant mucosal immune activation is a component in of the pathogenesis of iSGS. Most critically, our work offers new targets for future therapeutic intervention. Level of Evidence: NA Laryngoscope, 126:E356–E361, 2016